Genomics yields biological and phenotypic insights into bipolar disorder - O'Connell, Kevin S; Koromina, Maria; van der Veen, Tracey; Boltz, Toni; David, Friederike S; Yang, Jessica Mei Kay; Lin, Keng-Han; Wang, Xin; Coleman, Jonathan R I; Mitchell, Brittany L; McGrouther, Caroline C; Rangan, Aaditya V; et al. (Nature, 2025)
Bipolar disorder is a leading contributor to the global burden of disease1. Despite high heritability (60-80%), the majority of the underlying genetic determinants remain unknown2. We analysed data from participants of European, East Asian, African American and Latino ancestries (n = 158,036 cases with bipolar disorder, 2.8 million controls), combining clinical, community and self-reported samples. We identified 298 genome-wide significant loci in the multi-ancestry meta-analysis, a fourfold increase over previous findings3, and identified an ancestry-specific association in the East Asian cohort. Integrating results from fine-mapping and other variant-to-gene mapping approaches identified 36 credible genes in the aetiology of bipolar disorder. Genes prioritized through fine-mapping were enriched for ultra-rare damaging missense and protein-truncating variations in cases with bipolar disorder4, highlighting convergence of common and rare variant signals. We report differences in the genetic architecture of bipolar disorder depending on the source of patient ascertainment and on bipolar disorder subtype (type I or type II). Several analyses implicate specific cell types in the pathophysiology of bipolar disorder, including GABAergic interneurons and medium spiny neurons. Together, these analyses provide additional insights into the genetic architecture and biological underpinnings of bipolar disorder.
Keywords: Black or African American; fenotyp; Male; kohortové studie; Chromosome Mapping; Genetic Predisposition to Disease; Phenotype; Hispanic or Latino; Cohort Studies; White; běloši; Genome-Wide Association Study; běloch; mužské pohlaví; Genomics; White People; černoši nebo Afroameričané; lidé; ženské pohlaví; mapování chromozomů; Humans; Hispánci a Latinoameričané; Female; genomika; bipolární porucha; genetická predispozice k nemoci; celogenomová asociační studie; Bipolar Disorder